The influence of green board, board size, ROA, and leverage ratio on green innovation - Hamamah, Cahya Umi; Juanda, Ahmad (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
This study examines the influence of the green board committee, board size, return on assets, and debt ratio on green innovation in 79 Indonesian companies listed on the stock exchange. Data analysis used multiple linear regression using STATA and showed that green board committees and larger board size encourage green innovation, while a high ROA also contributes positively. In contrast, a high debt ratio inhibits green innovation. These findings indicate that firms need to balance between good governance, solid financial performance, and debt risk management to effectively adopt green innovation. Previous studies tend to focus on non-financial factors such as the Green Board Committee and Board Size, while research examining the interaction between non-financial and financial factors in driving GI is still very limited, especially in Indonesia. In fact, a comprehensive understanding of the combined influence of non-financial and financial factors is essential to effectively drive GI adoption.